Four new species from the diatom genus Kobayasiella Lange-Bertalot from waterbodies of Southeast Asia. Issue 4 (1st October 2020) - Glushchenko, Anton; Kociolek, John Patrick; Kuznetsova, Irina; Kulikovskiy, Maxim
Abstract : Six species of the genus Kobayasiella were found from waterbodies of Southeast Asia. Among them, four species were new to science and their formal descriptions are presented, illustrated with light and scanning electron micrographs. These are: K. laosica Glushchenko, Kulikovskiy & Kociolek sp. nov., K. vietnamensis Glushchenko, Kulikovskiy & Kociolek sp. nov., K. lamii Glushchenko, Kulikovskiy & Kociolek sp. nov. and K. vientianensis Glushchenko, Kulikovskiy & Kociolek sp. nov. In addition, two species of uncertain taxonomic status were observed: K. cf. parasubtilissima (H. Kobayasi & T. Nagumo) Lange-Bertalot and K. cf. saxicola (Manguin ex Kociolek & Reviers) Moser, Lange-Bertalot & Metzeltin. We compare these four species with similar taxa. These records represent the first known occurrences of the genus in waterbodies of Southeast Asia.